Austere Foreign Body Injuries in Children and Adolescents: A Characterization of Penile, Rectal, and Vaginal Injuries Presenting to Emergency Departments in the United States From 2008 to 2017. Issue 12 (December 2021) - Fischer, Julie; Krishnamurthy, Jayasree; Hansen, Shana; Reeves, Patrick T.
Abstract : Background: Pediatric foreign body (FB) injuries to the nasal, aural, and/or oral cavities are well documented. Description of austere foreign body (AFB) injuries involving the rectum, vagina, or penis eludes the current pediatric literature. Austere FBs can be difficult to identify and have the potential to cause serious consequences. We aim to characterize AFB injuries by children and adolescents presenting to emergency departments (EDs) in the United States. Methods: The National Electronic Injury Surveillance System was queried to include subjects aged 0 to 25 years using a primary search term for diagnosis of foreign body from the period of January 2008 to January 2017. The consumer product and the body part involved (ie, rectal, vaginal, penile) were analyzed. Taylor series linearization generated national estimates. A trend analysis was performed using the Cochrane Armitage test of trend. Results: There were 27, 755 (95% confidence interval, 21, 170–34, 338) national estimated childhood ED visits for suspected AFB injuries during 2008 to 2017 including an estimated 7756 vaginal FBs, 7138 penile FBs, and 8359 rectal FBs (RFBs). Over the timeline, there was a significant up trend in the frequency of annual RFBs ( P < 0.01). Conclusion: Austere FB injuries appear to cluster around age of 7 years. Most AFB injuries are able to be treated and released from the ED. It appears that RFB injury frequencies are rising and tend to require more frequent admission. Providers must be vigilant in the diagnosis and management of these potentially hazardous injury types.